Workplace Harassment and Job Satisfaction: A Sociological Study among Female Employees of Quetta (Balochistan) - Shabana Muhammad Anwar; Anam Aqil Khan; Qurratul Ain Sardar (Journal of Management Practices, Humanities and Social Sciences, 2021)
This study focused on the impact of workplace harassment on the job satisfaction of female workers. Harassment is a common issue in every level of employment. Workplace harassment includes verbal, psychological, and physical torture to harass working women. Women face abusive situations at the workplace based on their class, caste, social status, sexual direction. Workplace bullying affects women’s level of job satisfaction. Job Satisfaction is the behavior of employees towards their experiences related to the services. This study aims to examine the effects of harassment on the job satisfaction of working women in Quetta (Balochistan). Therefore, the sample was selected from higher educational institutes and educational directorates of Quetta. The structured questionnaire was distributed among 500 female workers. The sample was drawn with the help of simple random sampling. The statistical package for social sciences (SPSS) version 24 was used to analyze the data. The results show a significant negative association between harassment and job satisfaction of females. The results of the study indicate that workplace harassment affects the level of satisfaction of women at the workplace. Harassment affects their mental and physical health and workplace performance. Working women turnover their jobs due to workplace bullying. This research will be helpful for legislation bodies, NGOs, different women development programs, economists to get information about the effects of workplace harassment on women’s job satisfaction.